Disparity in Judge Decisions in Resolving Rad Inheritance Disputes: Case Study at the Sharia Court in Banda Aceh City - Hasballah, Khairuddin; Mubarrak, Dhaiful; Rassanjani, Saddam (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Two contrasting viewpoints emerge over the issue of rad inheritance, notably concerning the events at the Syar'iyah Court. One viewpoint granted Baitul Mal the remaining inheritance, while the other viewpoint maintained that the heirs were entitled to reclaim their remaining assets. This study aims to identify the key elements considered by the justices of the Aceh Syar'iyah Court and the Banda Aceh Syar'iyah Court while making their verdicts in this case, as well as how Islamic law assesses the resolution of inheritance disputes related to property rights. This study scrutinizes the empirical legal research methodologies employed by analyzing them from the perspective of Islamic legal theory. The data is collected by conducting interviews and accessing material in libraries. The findings indicate that the Banda Aceh Sharia Court's Panel of Judges awarded the remaining inheritance to Baitul Mal, in accordance with the book Hasyiyah al-Bajuri, Qanun Number 11 of 2002, and Article 11 paragraph (1), and Article 14 of Aceh Qanun Number 7 of 2004, which pertain to the implementation of Islamic Sharia in the fields of Aqidah, Worship, and Islamic Sharia, and Zakat Management, respectively. Per Article 193 KHI, the justices of the Aceh Syari'yah Court hold a differing opinion regarding the distribution of any leftover inheritance to the heirs of the zawil furudh. According to Islamic family law, Zaid bin Thabit and a few Malikiyah and Syafi'iyah jurists endorse the choice of Baitul Mal to accept the remaining bequest. Furthermore, Uthman bin Affan's viewpoint about the application of rad, which includes marital relations, asserts that all furudhheirs possess the right to rad. This stance is also backed by the ruling of the Panel of Judges of the Aceh Syar'iyah Court.